A simple vitrification technique for sheep and goat embryo cryopreservation - Gibbons, A. (2011)
The aim of this study was to evaluate pregnancy and embryo survival rate of vitrified in vivo produced Merino sheep and Criolla goat (morulae and blastocysts) embryos, using the plastic tips of micropipettes, as containers (Cryo-tips). The embryos were exposed, at room temperature, to two successive equilibration solutions for a period of 5 min and then to a vitrification solution (VS) for 30 s. Then embryos were then loaded in 1 μl VS, into a plastic micropipette tip, and plunged into liquid nitrogen. On thawing, the embryos were warmed (37 °C) and placed into cryoprotectant dilutions (three-step-process). In the ovine, the morula and blastocyst pregnancy rates (47.1% vs 50%) and embryo survival rates (41.2% vs 50%) recorded were similar for both embryonic stages. Unlike the sheep, no pregnancies were recorded in goat vitrified/thawed morulae embryos, following transfer. However, in contrast, goats receiving blastocysts recorded high rates of pregnancy and embryo survival (64% and 64%, respectively). This technique allows for easy handling of cryopreserved embryos, is simple and efficient in both ovine embryo stages and also for goat vitrified blastocysts. The technique has definite potential application.